Psyllium husk mucilage as a novel seed encapsulant for agriculture and reforestation - Cameron Dingley; Peter Cass; Benu Adhikari; Prajakta Bendre; Nitin Mantri; Fugen Daver (Journal of Sustainable Agriculture and Environment)
Abstract Introduction An efficient, economical, and flexible reforestation system capable of uncrewed aerial vehicle (UAV) deployment is a global necessity. Hydrogels have been previously investigated for their use in agriculture, however, research is limited in terms of UAV deployment. Psyllium Husk Mucilage (PHM) a natural hydrogel seed mucilage, has been previously investigated in other agricultural settings and shows promise in fulfilling the needs of UAV seeding. Materials and Methods A greenhouse trial was conducted under controlled laboratory conditions using two soil conditions 50% and 90% field capacity. PHM and bentonite clay blends containing dextran (DEX) and sodium alginate (SA) were tested for efficacy for two agricultural crops Green beans (Phaseolus vulgaris) and Lebanese cucumber (Cucumis sativus), as well as three Australian native species Acacia stenophylla, Cymbopogon refractus, and Eucalyptus coolabah. Agricultural Trials were conducted across a 4‐week period, whilst A. stenophylla was 8 weeks, and C. refractus and E. coolabah was 12 weeks. Results Utilisation of PHM had varying effectiveness based on seed and soil moisture. In nonagricultural seed trials, PHM hydrogel succeeded with A. stenophylla but dried out and rotted in the extended trials with C. refractus and E. Coolabah, leading to plant death. The encapsulated agricultural seeds were largely outperformed in growth trials by C‐Planted at 50% FC, and C‐Surface at 90% FC. Conclusion PHM exhibits potential for successful UAV seeding in low‐moisture agricultural conditions and is promising for fast‐germinating plants or other riverbank species with high water content requirements. Without extending degradation time PHM is not suitable for slow‐growing species.